Religious Values in Children: Does Parenting Really Have a Significant Influence in its Formation? - Prima Dewi Pratiwi (ijd-demos, 2022)
AbstractThe purpose of this study was to analyze the influence of parenting patterns in the formation of religious values in children. This study uses a qualitative-descriptive type of research with a case study approach. The object of this research. The object of this research is Pondok Qur'an which is located in X regency. The types of data used in this research are primary data and secondary data. Primary data was collected through interview method while secondary data came from literature study. Religious moral values are important because if people have morals then all attitudes and behavior are of course good, these moral values cannot be separated from how the role of parents in implementing good parenting, of course, to apply these moral values must be applied early on to children. because of all his attitudes and behavior, of course he imitates or sees from how his parents 'daily lives, therefore the first is how the parents' behavior is at home because if the behavior is good and correct, the example applied to the child is definitely good and vice versa if parents ignore the moral values of the religion it will have an impact on their children.Keyword: Parents, Parenting, Method, Type AbstrakTujuan penelitian ini adalah untuk menganalisis pengaruh pola asuh orang tua dalam pembentukan nilai-nilai agama pada anak. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif dengan pendekatan studi kasus. Objek penelitian ini. Objek penelitian ini adalah Pondok Qur'an yang terletak di Kabupaten X. Jenis data yang digunakan dalam penelitian ini adalah data primer dan data sekunder. Data primer dikumpulkan melalui metode wawancara sedangkan data sekunder diperoleh dari studi kepustakaan. Nilai moral agama menjadi penting karena jika manusia memiliki akhlak maka semua sikap dan perilaku tentunya baik, nilai moral tersebut tidak lepas dari bagaimana peran orang tua dalam menerapkan pola asuh yang baik tentunya untuk menerapkan nilai-nilai moral tersebut harus diterapkan sejak dini. untuk anak-anak. karena segala sikap dan tingkah lakunya tentu saja ia meniru atau melihat dari bagaimana keseharian orang tuanya, maka dari itu yang pertama adalah bagaimana tingkah laku orang tuanya di rumah karena jika tingkah laku tersebut baik dan benar maka keteladanan yang diterapkan pada anak adalah pasti baik dan sebaliknya jika orang tua mengabaikan nilai-nilai moral agama maka akan berdampak pada anak-anaknya.Kata kunci: Orang Tua, Pengasuhan, Metode, Jenis